You just don't get it bridging the schism between development and security priorities in XML development. - Nash, Andrew (SOA webservices journal.)
There are many reasons why security professionals and application developers seem to work at cross-purposes when bringing XML Web Services to production. By understanding the key differences in approach and the way to bridge them, organizations can realize significant time-to-market and cost benefits without compromising security and compliance needs.